2017
DOI: 10.4274/tjps.13008
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vivo</i> Effects of Naringenin and Lead on Rat Erythrocyte Carbonic Anhydrase Enzyme

Abstract: ÖZAmaç: Karbonik anhidraz (CA) enzimi CO 2 'nin su ile tersinir reaksiyonunu katalizler ve sistemik asit baz dengesi, solunum gibi metabolik açıdan oldukça önemli olaylarda görev alır. Bu çalışmada canlıların farklı yollarla maruz kaldığı bir ağır metal olan kurşun ile bir flavanon olan naringeninin enzim üzerine in vivo etkisi araştırıldı. Gereç ve Yöntemler: Bu amaçla, dört farklı sıçan grubu oluşturuldu ve bunlardan biri kontrol grubu olarak belirlendi. Diğer üç gruba ise kurşun, naringenin ve kurşun+naring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It was reported that CA activity in rat erythrocytes was significantly decreased exposed to naringenin, a natural flavone. In addition, it is known that the extracts containing polyphenols and flavones obtained from various plants and fungal species inhibit the activities of CA I and II (9). Inhibitory effects of the different extracts from Alcea dissecta on hCA I and II were determined for the first time in this study.…”
Section: Esterase Activitymentioning
confidence: 90%
See 1 more Smart Citation
“…It was reported that CA activity in rat erythrocytes was significantly decreased exposed to naringenin, a natural flavone. In addition, it is known that the extracts containing polyphenols and flavones obtained from various plants and fungal species inhibit the activities of CA I and II (9). Inhibitory effects of the different extracts from Alcea dissecta on hCA I and II were determined for the first time in this study.…”
Section: Esterase Activitymentioning
confidence: 90%
“…Carbonic anhydrases (CAs, EC 4.2.1.1) as ubiquitous widespread metalloenzymes catalyze the crucial reaction for all living organisms: the hydration process of CO 2 to HCO 3 -and H + (8,9). Fifteen isoenzymes of CA encoded from the α-CA gene family have been identified and characterized for human beings as cytosolic forms (hCA I, II, III, VII, and XIII), membrane-bound forms (hCA IV, IX, XII, and XIV), mitochondrial forms (hCA VA and VB).…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Carbonic anhydrase (CA, EC 4.2.1.1) is a metalloenzyme including Zn 2+ in the active region, found in all living species, which catalyzes the reversible conversion of carbon dioxide to bicarbonate and H + . 23 This reaction plays a critical role in many physiological processes associated with metabolic pathways, including carbon dioxide. 24 Therefore, the regulation of enzyme activity has emerged as an approach in the treatment of diseases such as neuropathic pain, 25 glaucoma, edema, idiopathic intracranial hypertension, 26 cerebral ischemia, 27 cancer, 28 and epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…In this condition, fluid secretion into the cysts and a malfunction in proliferation cause kidney cysts to form. 23 About 85% of instances of ADPKD are caused by "TRPP1 (polycystic kidney disease-1)" gene and protein mutations, while 15% are due to TRPP2 (PKD2) protein and gene mutations. 24 We thus investigated the role of TRPP2 in naringenin's As a follow-up to our first findings in Dictyostelium, we examined the influence effects on cyst development and "Madin-Darby canine kidney (MDCK)" cell proliferation.…”
mentioning
confidence: 99%